2018
DOI: 10.1097/hp.0000000000000937
|View full text |Cite
|
Sign up to set email alerts
|

Reflections on Basic Science Studies Involving Low Doses of Ionizing Radiation

Abstract: Investigation of health effects of low doses of radiation as a field of study has been riddled with difficulties since its inception. In this document we will use 100 mGy as the cutoff upper limit for low-dose radiation, borrowing this definition from the U.S. Department of Energy, although other agencies and researchers sometimes include up to five‐fold higher doses under the same title. Difficulties in this area of research are most often ascribed to the fact that effects of low doses of radiation are subtle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…Recent studies with animal models have made significant contributions to provide quantitative data and mechanistic insights [ 7–9 ]. The application of animal data to human populations remains in debate, but, the information, including the biological mechanisms, is apparently the clue to understand the dose-rate effects of ionizing radiation comprehensively [ 10 , 11 ]. Thus, the aim of the current review is to compile the animal studies, mostly rodent studies, with respect to the dose-rate-dependent adverse effects.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies with animal models have made significant contributions to provide quantitative data and mechanistic insights [ 7–9 ]. The application of animal data to human populations remains in debate, but, the information, including the biological mechanisms, is apparently the clue to understand the dose-rate effects of ionizing radiation comprehensively [ 10 , 11 ]. Thus, the aim of the current review is to compile the animal studies, mostly rodent studies, with respect to the dose-rate-dependent adverse effects.…”
Section: Introductionmentioning
confidence: 99%
“…Investigation of health effects of low doses of radiation (mainly 100 mGy as cutoff) as a field of study has been riddled by difficulties since its inception (Paunesku & Woloschak 2018). This is most often ascribed to the fact that effects of low doses of radiation are subtle and difficult to distinguish from the glut of other "low grade" stresses.…”
Section: Low Level Radiation (Llr)mentioning
confidence: 99%
“…Among the bio-molecules damages, DNA damage has been shown to be most important and to contribute maximally to cell death [15,16]. Studies made on DNA irradiated in vitro in solution, in the dry state or in vivo in the biological system have revealed that radiation causes a spectrum of damages to DNA.…”
Section: Effects Of Ionizing Radiation On Bio-moleculesmentioning
confidence: 99%